Le film de tournage shakespearien : fiction documentarisée ou documentaire fictionnalisé ? - Sarah Hatchuel (Sillages Critiques)
This essay aims to reveal the aesthetic and ideological stakes of the documentaries on the shooting of Shakespearean adaptations, in relation to the dialectics governing fiction and nonfiction, disclosure of enunciation or submersion into fiction. After reflecting upon the concepts of “documentary” and “fiction”, and upon the crucial role of the audience in the creation of a “reading contract”, the essay will focus on a specific “making of”—A Little Touch of Harry: The Making of Kenneth Branagh’s Henry V. This “making of” blurs the boundary between fiction and nonfiction by offering a “documentarizing” reading of excerpts from the fiction film and a “fictionalizing” reading of the documentary. It transforms the shooting of the feature film into a suspense narrative in which the director becomes a double of the hero in the fiction. The disclosure of illusion is framed by a wish to channel the spectators’ reception, in a filmic discourse that attempts to turn the author’s point of view into an authoritative voice.